# Rekenregels machten

#### Pas de correcte rekenregel(s) van machten toe [en reken uit indien mogelijk]

1. $$(-6x^{2})^{-6}$$
2. $$(\frac{4}{3}b)^{4}:(\frac{4}{3}b)^{7}$$
3. $$(-4y^{10})^{9}$$
4. $$(2c)^{-4}.(2c)^{-6}$$
5. $$-(-\frac{13}{4})^{-4}$$
6. $$(-\frac{6}{5})^{-1}$$
7. $$(\frac{10}{11})^{-8}.(\frac{2}{19})^{-8}$$
8. $$-(-2)^{-5}$$
9. $$(\frac{20}{19})^{6}.(\frac{13}{7})^{6}$$
10. $$(-9a^{8})^{4}$$
11. $$(\frac{13}{9})^{-2}.(\frac{4}{19})^{-2}$$
12. $$-(-\frac{20}{7})^{-2}$$

#### Pas de correcte rekenregel(s) van machten toe [en reken uit indien mogelijk]

##### Verbetersleutel

1. $$(-6x^{2})^{-6}=(-6)^{-6}.(x^{2})^{-6}=(\frac{1}{-6})^{6}.(\frac{1}{x^{2}})^{6}=\text{ZRM}\left[=\frac{1}{46656} \frac{1}{x^{12}}\right]$$
2. $$(\frac{4}{3}b)^{4}:(\frac{4}{3}b)^{7}=(\frac{4}{3}b)^{4-7}=(\frac{4}{3}b)^{-3}=(\frac{3}{4}\frac{1}{b})^{3}=\text{ZRM}\left[ =\frac{27}{64} \frac{1}{b^{3}} \right]$$
3. $$(-4y^{10})^{9}=(-4)^{9}.(y^{10})^{9}=\text{ZRM}\left[=(-262144)y^{90}\right]$$
4. $$(2c)^{-4}.(2c)^{-6}=(2c)^{-4+(-6)}=(2c)^{-10}=(\frac{1}{2}\frac{1}{c})^{10}\left[=\frac{1}{1024} \frac{1}{c^{10}}\right]=\text{ZRM}$$
5. $$-(-\frac{13}{4})^{-4}=-(-\frac{4}{13})^{4}=-\frac{4^{4}}{13^{4}}=\text{ZRM}\left[=-\frac{256}{28561}\right]$$
6. $$(-\frac{6}{5})^{-1}=(-\frac{5}{6})^{1}=-\frac{5^{1}}{6^{1}}= \left[=-\frac{5}{6}\right]$$
7. $$(\frac{10}{11})^{-8}.(\frac{2}{19})^{-8}=(\frac{10}{11}\frac{2}{19})^{-8}=(\frac{20}{209})^{-8}=(\frac{209}{20})^{8}=\text{ZRM}=\left[\frac{3640577568861717121}{25600000000}\right]$$
8. $$-(-2)^{-5}=-(-\frac{1}{2})^{5}=+\frac{1^{5}}{2^{5}}=\text{ZRM}\left[=\frac{1}{32}\right]$$
9. $$(\frac{20}{19})^{6}.(\frac{13}{7})^{6}=(\frac{20}{19}\frac{13}{7})^{6}=(\frac{260}{133})^{6}=\text{ZRM}=\left[\frac{308915776000000}{5534900853769}\right]$$
10. $$(-9a^{8})^{4}=(-9)^{4}.(a^{8})^{4}=\text{ZRM}\left[=6561a^{32}\right]$$
11. $$(\frac{13}{9})^{-2}.(\frac{4}{19})^{-2}=(\frac{13}{9}\frac{4}{19})^{-2}=(\frac{52}{171})^{-2}=(\frac{171}{52})^{2}=\left[\frac{29241}{2704}\right]$$
12. $$-(-\frac{20}{7})^{-2}=-(-\frac{7}{20})^{2}=-\frac{7^{2}}{20^{2}}\left[=-\frac{49}{400}\right]$$
Oefeningengenerator vanhoeckes.be/wiskunde 2023-06-07 17:44:42